(untitled) (mathematica didactica, 2014)
Currently, various measures are taken to orientate the university teacher training program for secondary school teaching more related to the later profession. In the evaluation study TEDS-Telekom student teachers from several universities were interviewed about their perceptions of university courses. A particular focus of the interviews was the question about the integration of visualization resp. vividness in mathematical courses. The results of the survey show that prospective teachers have a broad spectrum of individually embossed notions of vividness and that the perceptions of vividness are associated with the specific learning motivation of the student teachers. Interpreting the results of the study from the perspective of mathematics education, within the contribution the vividness will be discussed in the theoretical framework of a didactic principle, which in an expanded form plays a major role in teacher education. Based on the results of the study implications for the improvement of teacher training programs are discussed.